Exploring Gotong Simalungun's Approach to Geometry Concepts at SMP Negeri 1 Dolok Batu Nanggar - Parsaulian, Benni Polin; Tambunan, Hardi (JUPE : Jurnal Pendidikan Mandala, 2025)
This research explores the traditional Simalungun carrying culture known as "Gotong" and its relationship with geometric concepts in mathematics. The study was conducted at SMP Negeri 1 Dolok Batu Nanggar and aims to uncover the geometric patterns, forms, and structures present in the traditional tools and practices of Gotong. Using ethnomathematics as the theoretical lens, the research employs a qualitative descriptive method involving field observations, interviews with cultural figures, and documentation analysis. The findings reveal that Gotong involves significant geometric reasoning, including symmetry, angles, polygons, and measurement estimation. This study contributes to the integration of local wisdom into geometry education and supports culturally responsive teaching practices in schools.